Relevansi Antara Hardiness dan Emotional Labor Pada Perawat Rumah Sakit Umum Daerah dr. Soegiri Kabupaten Lamongan - Badarul Ullah, Bagas; Budiani, Meita Santi (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
One of the determinants of the quality of a hospital is improved service. Adjustment of actions, behavior, facial expressions of nurses in performing services in the workplace is called Emotional Labor. This will have an impact on the psychological and work environment. However, nurses with certain characteristics will be able to achieve adjustment of actions, behavior, facial expressions while doing work without psychological impact. This study aims to determine the relationship between hardiness and emotional labor for nurses in general inpatient wards. The method used in this research is quantitative. The number of general inpatient nurse population is 114 nurses. The scale trial conducted by 30 nurses was taken from 10 public rooms with the same percentage. The subjects used in this study consisted of 84 nurses. Instruments on the emotional labor scale are arranged based on aspects of Hochschild (2012), totaling 20 items. Meanwhile, on the hardiness scale based on aspects from Stein & Bartone (2020), 18 items were found. Product-moment analysis technique is used to measure the correlation of the two variables. The results of this study showed a significant correlation of 0.000 (<0.05). It means that it can be said that there is a relationship between hardiness and emotional labor for nurses who work in the inpatient room of RSUD dr. Soegiri, Lamongan Regency. This can happen because a good emotional workforce nurse will be able to encourage an increase in the quality of hospital services, but the impact of this emotional workforce will be able to reduce if individuals have resilient characteristics with commitment, control and challenges.